Environmental Assessment Organization By Using A Combined Approach Of Fuzzy Ahp And Swot Analysis Case Study: Health Network Of Kashan University Of Medical Science - Rahati, Meghdad; Dehghani, Masoud; Razzaghi, Reza; Nanakar, Reza; Sakeni, Zahra; Kavosian, Abas; Dehaghi, Zahra Hashemi (The Turkish Online Journal of Design Art and Communication, 2016)
Today's, one of the secrets to success in organizations is power of analysis. Analysis of strengths, weaknesses, opportunities and threats is an appropriate tools. As regards the importance of each above factors is equal in prioritizing and decision making, in this study, researchers had certain importance and weight of each factors quantitatively with combined approach of Fuzzy AHP and SWOT Analysis. In this applicable, cross-sectional and descriptive study, that had been done in Health Network of Kashan University of Medical science, were used three questionnaires for data collection and was conducted during the four steps: 1.Identification environmental factors 2. Measurement environmental factors (main criteria) 3. Calculate the Weight of sub criteria (Level two) 4. Finalizing weight of each factor. In the ranking of environmental factors, Fuzzy AHP method has been used. In this study between environmental factors, Weaknesses, had highest weight. Also in analysis of environmental Health Network, Weaknesses in finance management (0/131) and appropriate distribution of age and education level of employment experts (0/085) had highest priority rank. In analysis of environmental factors by using a combined approach of Fuzzy AHP and SWOT Analysis ,by giving weight and degree in internal and external factors, can be obtain more precise results than SWOT method.
Keywords: Fuzzy hierarchical analysis; SWOT analysis; synthesis models SWOT